2014
DOI: 10.1108/medar-09-2013-0039
|View full text |Cite
|
Sign up to set email alerts
|

Accountants’ perceptions of corporate governance in public limited liability companies in an emerging economy

Abstract: Purpose – This paper aims to examine the perceptions of accountants on corporate governance (CG) practices in public limited liability companies in Barbados, and the perceived effectiveness of these mechanisms. Design/methodology/approach – A three-stage approach was utilized. First, an Internet-based questionnaire was sent to members of the Institute of Chartered Accountants of Barbados to gain accounting perspectives on CG practices by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…It is, however, possible that analysts and investors in SA pay particular attention to other performance indicators, such as revenue and headline earnings per share (which is regulatory disclosure requirement unique to SA). The difference may also be attributable to the crucial strides that have been made globally in corporate governance consciousness since the dawn of the major accounting scandals (Alleyne, Weekes-Marshall & Broome, 2014). Lastly, within the research design, the earnings and change in earnings variables have not been adjusted for the asymmetric effects of negative special items and the applicable effective tax rates for profit and loss companies, owing to data constraints.…”
Section: Resultsmentioning
confidence: 99%
“…It is, however, possible that analysts and investors in SA pay particular attention to other performance indicators, such as revenue and headline earnings per share (which is regulatory disclosure requirement unique to SA). The difference may also be attributable to the crucial strides that have been made globally in corporate governance consciousness since the dawn of the major accounting scandals (Alleyne, Weekes-Marshall & Broome, 2014). Lastly, within the research design, the earnings and change in earnings variables have not been adjusted for the asymmetric effects of negative special items and the applicable effective tax rates for profit and loss companies, owing to data constraints.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, corporate governance disclosures of listed companies are voluntary. Meanwhile, major issues of corporate governance in Barbados include the lack of a formal governance framework, interlocking directorships and a bias in the selection of individuals to serve on various boards (Alleyne et al, 2014).…”
Section: Legal Overview Of Corporations In Barbadosmentioning
confidence: 99%
“…In the Caribbean, there were similar occurrences of failures and collapses of companies that promoted unethical behaviour. For example, the failure of CLICO and the collapse of the Allen Stanford Empire in Antigua for engaging in a Ponzi scheme caused attention to be focused on bad management practices which resulted in financial burdens being placed on governments and investors within the region (Alleyne et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in these areas should be of interest to international communities as trading partners to these entities, and hence, the collapse of large regional companies such as CL Financial Holdings, Colonial Life Insurance Company (CLICO), and the Stanford Group of Companies have all shown that there is a need to research existing models of CG and RM practices in developing economies. Barbados is highly under‐researched in these areas with only a few studies focusing on accountant's perceptions of CG (Alleyne, Weekes‐Marshall, & Broome, 2014); audit committees (Alleyne, Howard, & Greenidge, 2006); external audit (Alleyne, Devonish, & Alleyne, 2006; Alleyne & Howard, 2005). Regional RM failures were examined by Soverall (2012), while Wood and Kellman (2013) examined RM practices in Barbadian banks.…”
Section: Introductionmentioning
confidence: 99%